Astragalus membranaceus extract attenuates ulcerative colitis by integrating multiomics and the PI3K/AKT signaling pathway - Zhu, Jiaying; Shentu, Chenhuan; Meng, Qingling; Fan, Sen; Tang, Yunjia; Mao, Mingjiang; Yuan, Xiaofeng (Frontiers in Pharmacology, 2025)
IntroductionUlcerative colitis (UC) is a chronic, non-specific inflammatory bowel disease (IBD) that severely impairs the quality of life of affected individuals. Astragalus membranaceus (Fisch.) Bge. [Fabaceae; Astragali radix] (AM), a widely used Chinese medicine, has active ingredients that exhibit significant anti-inflammatory effects. This study aimed to investigate the role of AM extract in alleviating dextran sulfate sodium (DSS)-induced colitis in mice.MethodsA UC model was established, and AM extract was orally administered to evaluate its role in the treatment of colitis in mice. The effects of AM extract on colitis mice were subsequently investigated via 16S rDNA profiling, as well as short-chain fatty acids (SCFAs) and bile acids (BAs) sequencing. In addition, network pharmacology approaches and supplementary validation experiments were conducted to elucidate the underlying mechanisms of action.ResultsAM extract notably alleviated UC-related symptoms, promoted the restoration of intestinal barrier integrity, and suppressed inflammation. Concurrently, it contributed to the rebalancing of the gut microbiota and normalization of both SCFAs and BAs metabolic processes. Mechanistic investigations integrating network pharmacology and experimental validation revealed that the beneficial effects of AM extract are likely mediated through the regulation of the PI3K/AKT signaling pathway.DiscussionOur study demonstrated that the AM extract effectively alleviated UC. The extract was shown to modulate microbial dysbiosis triggered by DSS and promote the generation of beneficial metabolites. Subsequent analyses confirmed that these effects are mediated through activation of the PI3K/AKT signaling pathway. Collectively, these findings offer novel insights into treatment strategies for UC.